Components, packaging and manufacturing technology II : selected, peer reviewed papers from the 2013 3rd International Conference on Packaging and Manufacturing Technology (ICCPMT 2013), December 31, 2013 - January 2, 2014, Brisbane Australia - Wu, Andy (Applied mechanics and materials ;, 2014)
Collection of selected, peer reviewed papers from the 2013 3rd International Conference on Components, Packaging and Manufacturing Technology (ICCPMT 2013), December 31, 2013 - January 2, 2014, Brisbane Australia. The 42 papers are grouped as follows: Chapter 1: Materials Science and Materials Processing Technology; Chapter 2: Mechanics; Chapter 3: Modelling, Design and Manufacturing; Chapter 4: Automation, Control, Information Technology and MEMS.